The Return to Straight-Line Depreciation: An Analysis of a Change in Accounting Method - Archibald, T. Ross (Journal of Accounting Research, 1967)
T. Ross Archibald, The Return to Straight-Line Depreciation: An Analysis of a Change in Accounting Method, Journal of Accounting Research, Vol. 5, Empirical Research in Accounting: Selected Studies 1967 (1967), pp. 164-180